Multiple myeloma in the real world settings: prognostic significance of 1q21 chromosomal abnormalities - single center experience - Sretenovic, Aleksandra; Mitrovic, Marko; Bukumiric, Zoran; Vukosavljevic, Nikola; Kecman, Natalija; Jovanovic, Jelica; Fekete, Marija Dencic; Zaric, Enisa; Bila, Jelena (Frontiers in Oncology, 2026)
BackgroundAlthough prognostic significance of 1q21 chromosomal abnormalities (CAs) in multiple myeloma (MM) has been validated, the real world data (RWD) of its practical utilization in the clinical practice remain to be of interest. The aim of study was to analyze the prognostic significance of 1q21 CAs in the RWD settings of the routine clinical practice.MethodsThe study included 328 newly diagnosed MM patients (NDMM, pts), diagnosed during the period 2018-2024. The distribution according to the second Revision of the International Staging System (R2-ISS) was 25.6%, 22.9%, 46.3% and 5.2% with scores 1, 2, 3 and 4, respectively. The 1q21 CAs, gain1q21 and amp1q21, were detected in 33.7% pts (gain1q21 in 12.4% pts, and amp1q21 in 21.3% pts). Patients were treated predominantly (238pts, 72.6%) with Bortezomib (Bz) plus immunomodulatory drugs (IMids) based triplets. Autologous stem cell transplantation (ASCT) were performed in 87/114 potential transplant candidates (76.3%).ResultsThe overall response rate (ORR ≥PR) was achieved in 86.3% of the patients, regardless of the findings of gain 1q21 (p=0.113) or amp1q21 (p=0.757) in comparison to the patients without 1q21 CAs. Patients without 1q21 CAs had significantly longer progression-free survival in comparison to the patients with gain 1q21 or amp1q21 (PFS, p=0.000). The overall survival of the patients with amp1q21 was significantly shorter in comparison to the patients with gain1q21 or those without 1q21 CAs (OS, p=0.043).ConclusionPresence of the 1q21 CAs retains clear impact on the course of disease in MM patients outside of clinical trials. As a part of validated prognostic indices, finding of 1q21 CAs represents valuable prognostic biomarker, which may contribute in bringing up treatment choice, especially in the circumstances of limited accessibility to the new treatment modalities.